EDUCATIONAL POTENTIAL OF YOUNG PEOPLE IN SERBIA FOR RELIGIOUS DIALOGUE AND TOLERANCE (Religious dialogue and cooperation, 2023)
Institutional education of young people for religious dialogue and tolerance inthe Republic of Serbia began with the introduction of optional teaching subjects ReligiousEducation and Civic Education in primary and secondary schools in 2001. At the sametime, a radical reform of the educational system was started in accordance with neoliberalideological principles and development strategies. Explicit and hidden religious andpolitical contents can also be observed in many other teaching subjects that have undergonereform changes in teaching contents, especially in primary education. Religiouseducation is conducted according to the confessional model for recognized churches andtraditional religious communities living in Serbia. As a general goal of Religious Education,it was pointed out that it should provide students with a complete religious view ofthe world and life, as well as enable them to freely adopt the spiritual and life values of theChurch or community to which they belong. Then, that this goal should be achieved inan open and tolerant dialogue, with respect for other religious experiences and views. Inthe tasks of Religious Education, it is indicated that it should develop in students the aspirationtowards responsible shaping of common life with other people, peoples, religiouscommunities and cultures different from their own. On the other hand, Civic Educationis defined as education for democracy and civil society. The main goal of teaching in thissubject is to acquire knowledge and develop skills for the role of a responsible citizen forlife in a democratically organized and humane society based on respect for human andcivil rights, the right to diversity and the development of multiculturalism. The teachingcontent in these, as well as in other complementary subjects, has been influencing theformation of basic value attitudes and rules of behavior for two decades, thus creating anew religious and political culture among young people that contributes to a more tolerantattitude towards many social issues and a better understanding of various social phenomenaand relationships. It is a well-founded assumption that young people studying inSerbia have the educational potential for religious dialogue and tolerance.
Keywords: Religious dialogue; Tolerance; Education; Serbia